Penggunaan Bahan Alam Sebagai Terapi Pereda Nyeri Dysminorrhea Pada Remaja : Review Artikel - Shipa Paujiah; Salman Salman; Indah Laily Hilmi (Journal of Pharmaceutical and Sciences, 2023)
Dysmenorrhea is a monthly problem for women because it can interfere with activities. Dysmenorrhea is a condition of cramping pain in the lower abdomen accompanied by other symptoms, such as headaches, nausea, et cetera, that occur 24 hours before menstruation and can last 24-36 hours. The prevalence of dysmenorrhea in Indonesia is 64,25%, with 54,89% as primary dysmenorrhea and 9,36% as secondary dysmenorrhea. Management of dysmenorrhea can be done with pharmacological and non-pharmacological. Therapy pharmacological can use NSAIDs, hormonal drugs, and pain medications. At the same time, therapy with non-pharmacological can use warm water, exercise, and natural materials as complementary therapy for dysmenorrhea pain relief therapy in a teenager. The goal is to determine what natural materials can be used for dysmenorrhea pain relief in teenagers by analyzing the frequency of pain degrees before and after being given natural materials. A methodological literature review of using natural materials as a complementary therapy for pain relief in a teenager with dysmenorrhea. The result is a change in the frequency of pain in each natural material given to teenagers. The conclusion is that temulawak, butterfly pea, soybean, tamarind, turmeric, ginger, carrot, pineapple, honey, coconut, and white turmeric extract have the potential as a complementary therapy for dysmenorrhea pain relief.